Scoping endangered futures: rethinking the political aesthetics of climate change in world risk society - Blok, Anders (STS Encounters, 2017)
In this article, I engage a key claim of Ulrich Beck’s theorizing of global risks, to the effect that socio-political collectivities are currently being re-imagined through the anticipation of endangered long-term futures. Such dynamics of temporal reordering are visible, the article shows, in the imaginative politics of climatic projections. To rethink the resultant political aesthetics of climate change, the article maps out the visual, experiential, and affective forms in which endangered climatic futures come to saturate public culture. Such encounters, the article suggests, constitute inter-media events, drawing on scientific, artistic, and mass media registers, and embodied in what Karin Knorr Cetina call scoping devices of information and visualization, involving particular ‘fateful’ time transactions. These conceptual suggestions are illustrated and elaborated by drawing on auto-ethnographic observations during a particular event of intense futurity, that of the international COP15 climate change conference held in Copenhagen during December of 2009.